Awareness and Practices of Mothers on Home Management of Acute Diarrhea in Children Under Five at Benghazi Children’s Hospital, Libya - Salma Elzwai; Reema Salih; Tahani Asnedel; Somaa Atiaya; Mabrouka Bofarraj (AlQalam Journal of Medical and Applied Sciences, 2025)
Diarrhea is a major contributor to mortality and morbidity among children under five years of age, particularly in developing countries. Despite the effectiveness of Oral Rehydration Solution (ORS) in avoiding dehydration, its proper use at the household level remains suboptimal due to limited maternal awareness and misconceptions. This study was carried out to assess the awareness, knowledge, and practices of mothers regarding home management of acute diarrhea among children under five years at Benghazi Children’s Hospital, Libya. This cross-sectional descriptive research was performed in 2023 at the Gastroenterology Department of Benghazi Children’s Hospital. A total of 100 mothers of under-five children with acute diarrhea were interviewed using a structured, pretested Arabic questionnaire covering socio-demographic data, knowledge, and home management practices. Information has been examined utilizing SPSS version 25, with p ≤ 0.05 deemed significant. Only 51% of mothers demonstrated adequate knowledge and practice regarding diarrhea management. Most (92%) continued breastfeeding during diarrhea, yet misconceptions persisted—65% believed excessive ORS is harmful, and 53% stored it improperly. Knowledge about zinc use was low (39%). Maternal age and number of children showed a significant positive correlation with knowledge level (p< 0.05), while education, income, and residence showed no significant association. Although awareness of diarrhea management was moderate, gaps in ORS preparation, danger sign recognition, and zinc use persist. Targeted health education programs are essential to improve mothers’ knowledge and home-based management practices.